2020
DOI: 10.3390/plants9020279
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Arbuscular Mycorrhizal Fungi Utilization in Production of Allium Plants

Abstract: The need to improve crop yield and quality, decrease the level of mineral fertilizers and pesticides/herbicides supply, and increase plants’ immunity are important topics of agriculture in the 21st century. In this respect, arbuscular mycorrhizal fungi (AMF) may be considered as a crucial tool in the development of a modern environmentally friendly agriculture. The efficiency of AMF application is connected to genetic peculiarities of plant and AMF species, soil characteristics and environmental factors, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 88 publications
1
18
0
2
Order By: Relevance
“…Despite the variability response of crops to the mycorrhizae application (Estaún, Calvet, & Camprubí, 2010;Kokkoris, Hamel, & Hart, 2019;Saia et al, 2020), our result is in line with number of studies related with significant contribution of mycorrhizae in increasing the crops yield (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014;Saleh, Anshary, & Made, 2018;Samanhudi, Yunus, Pujiasmanto, Cahyani, & Lestariana, 2017;Wang et al, 2019). This study also confirmed the importance of AM application on the allium species that have limited expansion of the root system as one obstacle to absorb sufficient nutrients for plant growth (Golubkina et al, 2020).…”
Section: Effect Of Mycorrhizae On Shallot Roots and Yieldssupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the variability response of crops to the mycorrhizae application (Estaún, Calvet, & Camprubí, 2010;Kokkoris, Hamel, & Hart, 2019;Saia et al, 2020), our result is in line with number of studies related with significant contribution of mycorrhizae in increasing the crops yield (Bhardwaj, Ansari, Sahoo, & Tuteja, 2014;Saleh, Anshary, & Made, 2018;Samanhudi, Yunus, Pujiasmanto, Cahyani, & Lestariana, 2017;Wang et al, 2019). This study also confirmed the importance of AM application on the allium species that have limited expansion of the root system as one obstacle to absorb sufficient nutrients for plant growth (Golubkina et al, 2020).…”
Section: Effect Of Mycorrhizae On Shallot Roots and Yieldssupporting
confidence: 91%
“…The great contribution of the AM on plant growth and crop production in the tropics has been reviewed by Naher, Othman, & Panhwar (2013). However, among horticulture crops, allium species are more sensitive to AM application due to their less growth root system, thus causing low absorption capability of soil nutrients (Golubkina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are ubiquitous soil microorganisms that establish mutualistic symbioses with the majority of land plants [ 1 ], including most agricultural crops [ 2 ]. AMF are considered an important tool in the modern environmentally friendly agriculture in the 21st century for the improvement of crop yield and quality and for the decrease of mineral fertilizers and pesticides/herbicides [ 3 ]. The main benefits of AMF to plants include improved acquisition and accumulation of nutrients (such as P and N); and to repay, host plants provide organic carbon to AMF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant exudates are mainly excreted from lateral roots, which also serve as entry points for nodulating bacteria or other beneficial endophytes [37,39]. Further indications for the second hypothesis are given by the fact the bulb plants have a specific lifecycle and are often associated with a mycorrhiza [25]. Interestingly, distinct Pseudomonas strains are known due to their positive interactions with certain fungi as "mycorrhiza helper bacteria" [40].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was shown that plants with bioactive secondary metabolites usually harbor highly specific microbial communities that are shaped by those substances [22][23][24]. Less is known about the bacterial component within the microbiome of the Amaryllidaceae plant family, while its mycorrhiza was already intensively studied [25]. Moreover, the microbiome of stored onions (Allium cepa) was recently explored by Yurgel and colleagues [26]; they identified Pseudomonas as a biomarker for healthy onions.…”
Section: Introductionmentioning
confidence: 99%